REASONABLE TIME LIMITS FOR CIVIL PROCEEDINGS AS A GUARANTEE OF HUMAN RIGHTS PROTECTION - Shvachka, Victoria (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
Purpose: to study the main aspects of realization of the individual’s right to access to justice by ensuring a prompt and efficient trial of civil cases; to analyze the content of the concept of “reasonable time”; to find out the main reasons for the excessive duration of the trial and to identify the main ways to resolve them. Research methods: in the course of preparing this article, the author used a system of philosophical, general scientific and special methods. In particular, to study the case-law of the European Court of Human Rights on defining the content of the concept of “reasonable time”, to clarify the degree of its certainty and to consolidate it at the level of national legislation, the author used the systematic and comparative legal methods of scientific research. The statistical and structural-systemic methods allowed the author to identify and systematize the main reasons for the excessive duration of court proceedings. Results: it was found that the main unresolved issues today are understaffing of the judiciary, turnover of support staff, low level of organizational and material support of judicial institutions, disconnection of judicial institutions from electricity supply, which results in the actual suspension of their activities. Discussion: the state must create all conditions for a citizen to have full access to justice in order to protect his or her violated or disputed right and to restore it quickly and effectively. Failure of courts to comply with reasonable time limits for consideration of civil cases leads to a violation of the constitutional right to judicial protection and Article 6 of the Convention for the Protection of Human Rights and Fundamental Freedoms, which is unacceptable in the context of the European development of the national legal system of Ukraine.